Oil and Gas Companies: Key Metrics and Stock Performance - Nguyễn, Hà Phương ([s. l.], 2020)
Key metrics of oil and gas exploration and production companies. Annual financial and operating data of key metrics and stock prices from some biggest oil and gas companies around the world. Analysis of correlation between stock price and each key metric of these companies. Multiple regression model